THE INFLUENCE OF MOTIVATION, TYPE OF JOB AND SOCIAL ENVIRONMENT ON THE UNDERSTANDING OF PROFESSIONAL ZAKAT IN MUARA ENIM DISTRICT - Indriyani, Selvi Dwi; Mismiwati, Mismiwati; Fakhrina, Fakhrina; Krisdayanti, Helicia; Riduwansah, Riduwansah (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
Abstract Research entitled The Influence of Motivation, Type of Work and Social Environment on Understanding Professional Zakat in Muara Enim District. Understanding is the ability of the community in Muara Enim District to understand and comprehend professional zakat. The aim of this research is to analyze motivation, type of work and social environment of society towards understanding professional zakat. In this study, the population used was people who work in Kepur Village, Muara Enim District. The research sample was taken from 100 of 361 people who work using a non-probability sampling technique using the formula Hair et al. In this research, a quantitative approach was used using data collection techniques by distributing questionnaire data. Data analysis techniques use SPSS 26.0 software tools. The results of this research are that the motivation variable influences the understanding of professional zakat with a t-count of 2.263 and a t-table of 1.661, the type of work influences the understanding of professional zakat with a t-count of 4.170 and a t-table of 1.661, the social environment influences the understanding of professional zakat with a t-count of 2.636 and a t-table of 1.661 and motivation , the type of work and social environment together influence the understanding of professional zakat in Muara Enim District.